Integration of Artificial Intelligence in Islamic Religious Education Learning: Opportunities, Challenges, and Implementation Strategies - Rif'ah Rif'ah; Ani Cahyadi (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the integration of Artificial Intelligence (AI) in Islamic Religious Education (IRE) learning by examining its opportunities, challenges, and implementation strategies within contemporary educational contexts. The research employs a qualitative library research method, drawing upon academic books, peer-reviewed journal articles, policy documents, and relevant digital resources discussing AI in education, Islamic pedagogy, and lifelong learning. Data were analyzed using content analysis techniques to identify major themes related to technological transformation, pedagogical adaptation, ethical considerations, and institutional readiness. The findings indicate that AI offers significant opportunities for enhancing personalized learning, adaptive assessment, intelligent tutoring systems, and digital content development in IRE. AI-based platforms can support differentiated instruction, facilitate access to classical and contemporary Islamic sources, and promote interactive learning environments. However, the study also reveals substantial challenges, including ethical concerns, algorithmic bias, data privacy risks, digital inequality, teacher competency gaps, and potential reduction of spiritual-human interaction in religious learning. Effective implementation requires strategic planning, professional development for educators, curriculum redesign, ethical governance frameworks, and alignment with Islamic educational values. The study concludes that AI integration in IRE must balance technological innovation with moral, spiritual, and humanistic dimensions to ensure meaningful and sustainable educational transformation.